Development of Mathematics learning tools through Realistic Mathematics Education (RME) to enhance spatial ability - Fince Putri Yeni Purba; Bornok Sinaga; Fauziyah Harahap (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to develop mathematics learning tools based on Realistic Mathematics Education (RME) to improve elementary school students’ spatial ability. The research was conducted in response to students’ low spatial skills, primarily caused by the dominance of conventional teaching methods, limited use of contextual media, and the absence of systematically integrated learning tools using the RME approach. The development procedure used a modified ADDIE model consisting of three main stages: analyze, design, and develop. The research subjects included fourth-grade students and mathematics teachers at SDN 102083 Pabatu. The instruments involved expert validation questionnaires, student response questionnaires, spatial ability tests, and observation sheets for lesson implementation. The results showed that the developed learning tools were deemed valid by material experts, media experts, and teachers. The high level of lesson implementation and positive responses from both students and teachers confirmed practicality. Effectiveness was evidenced by the improvement in pretest and posttest scores, with a normalized gain score of 0.651 and a classical mastery percentage of 88 percent. These findings suggest that RME-based learning tools are effective in enhancing students’ spatial abilities in Mathematics. Abstrak Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran Matematika berbasis Realistic Mathematics Education (RME) guna meningkatkan kemampuan spasial murid sekolah dasar. Latar belakang penelitian ini adalah rendahnya kemampuan spasial murid yang disebabkan oleh dominasi metode pembelajaran konvensional, penggunaan media yang kurang kontekstual, serta belum tersedianya perangkat ajar yang mengintegrasikan pendekatan RME secara sistematis dan menyeluruh. Prosedur pengembangan menggunakan model ADDIE yang dimodifikasi menjadi tiga tahap utama, yaitu analyze, design, dan develop. Subjek penelitian meliputi murid kelas IV SDN 102083 Pabatu dan guru mata pelajaran Matematika. Instrumen yang digunakan mencakup angket validasi, angket respon, tes kemampuan spasial, dan lembar observasi keterlaksanaan. Hasil penelitian menunjukkan bahwa perangkat pembelajaran yang dikembangkan dinyatakan valid berdasarkan penilaian ahli materi, ahli media, dan guru. Perangkat juga tergolong praktis karena keterlaksanaan pembelajaran mencapai kategori baik dan memperoleh respon positif dari guru dan murid. Keefektifan perangkat dibuktikan melalui peningkatan nilai pretest dan posttest, dengan skor N-Gain sebesar 0,651 dan persentase ketuntasan klasikal sebesar 88%. Hasil tersebut menunjukkan bahwa perangkat pembelajaran berbasis RME efektif dalam meningkatkan kemampuan spasial murid sekolah dasar.Kata Kunci: kemampuan spasial; perangkat pembelajaran; Realistic Mathematics Education; RME; sekolah dasar